Foreign Exchange Return Predictability: Rational Expectations Risk Premium vs. Expectational Errors - Seongman Moon (East Asian Economic Review (EAER), 2018)
We propose a simple identification scheme for the causes of the violations of uncovered interest parity. Our method uses the serial dependence patterns of excess returns as a criterion for judging performance of economic models. We show that a mean reverting component in excess returns, representing a violation of uncovered interest parity, mainly contributes to generating different serial dependence patterns of excess returns: rational expectations risk premium models tend to generate negative serial dependence of excess returns, while expectational errors models tend to generate positive serial dependence.
Keywords: F31; F37; G15; 330; Violations of Uncovered Interest Parity; Expectational Errors; Rational Expectations Risk Premium; Foreign Exchange Excess Returns; Serial Dependence